Pedagogical Competence of Christian Religious Education Teachers in Implementing the Merdeka Curriculum in Indonesia - Dwi Ariefin; Mariani Harmadi; Mareyke Maritje Wagey Tairas; Dwi Anugrahani Handayani (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The Independent Curriculum demands a shift in educational emphasis toward creative, innovative, and differentiated learning across the dimensions of planning, implementation, and assessment. However, nationally, empirical data on the pedagogical competence of Christian Religious Education (CRE) teachers in implementing this curriculum is still limited. This study aims to identify the pedagogical competence of Christian Religious Education (CRE) teachers in classroom learning within the context of the Independent Curriculum. This research is a quantitative study with a national survey design. Data were collected through an online questionnaire distributed to 164 Christian Religious Education (CRE) teachers at the junior high school level selected from a total population of 8,770 Christian Religious Education (CRE) teachers in Indonesia. The research instrument was a pedagogical competency questionnaire covering three main dimensions: planning, implementation, and assessment of learning. Data analysis used descriptive and inferential statistics. The results show that the pedagogical competence of Christian Religious Education (CRE) teachers is in the high and very high categories. Teachers who are not tied to the old curriculum pattern tend to be more flexible in adopting innovative learning procedures. In the context of Christian Religious Education, pedagogical competence encompasses not only the technical aspects of learning but also the responsibility to guide students' holistic development. The implications of this research emphasize that strengthening the pedagogical competence of Christian Religious Education teachers needs to be directed toward ongoing professional, reflective, and spiritual development to support the successful implementation of the Independent Curriculum.